Continuous Measurement of Moisture in Timber - Pope, D.J.; Taylor, G.D. (Structural survey, 1994)
Reports on a research programme, undertaken at the Structural Timber Research Unit of the University of Brighton, UK, which aimed to provide information on the long-term structural performance of Glulam timber. In particular, addresses the issue of continuously measuring the moisture content of beams undergoing creep testing in a cyclic humidity environment. Suggests that the method of testing described could be of particular use in situations where there is limited access and where there is a history of moisture penetration associated with unusual roof designs and older buildings subject to preservation orders.